High‐Performance Thermoresponsive Dual‐Output Dye System for Smart Textile Application. (28th October 2019) - Zhang, Wan; Ji, Xiaozhou; Peng, Bo‐Ji; Che, Sai; Ge, Fangqing; Liu, Wenwen; Al‐Hashimi, Mohammed; Wang, Chaoxia; Fang, Lei
Abstract: Smart textiles exhibiting optical response to external temperature stimuli are promising functional materials for a wide range of applications. It is critical yet challenging to endow these materials with high‐contrast, vivid, and real‐time optical signals, such as changes in color or fluorescent emission, for the indication of heating and/or cooling. A thermoresponsive dye system featuring simultaneous thermochromism and thermofluorescence is developed and applied to dyeing of polyester fabrics. The dye system is constructed by encapsulating a solution of indenoquinacridone (IQA) in aliphatic alcohol into SiO2 nanoparticles. The dual‐output response relies on the mechanism of solvent‐modulated dissociation/aggregation of the IQA molecules. Upon heating, the dye system and the dyed fabric exhibit clear color change and high‐contrast, turned‐on fluorescence, in a real time and highly reversible manner. The thermoresponsive temperature can be tailored by varying the aliphatic alcohol solvent with different melting point. The integration of high‐contrast dual optical outputs into this programmable, robust, and reversible dye system lays the foundation for its employment in a wide range of challenging applications in smart textiles. Abstract : Solvent‐modulated dissociation/aggregation of a quinacridone derivative leads to simultaneous thermochromism and thermofluorescence. After encapsulation into SiO2 nanoparticles, the system can be dyed into polyester fabrics. Upon heating, the dyed textiles exhibit clear color change and high‐contrast, turned‐on fluorescence, in a real‐time and highly reversible manner. The thermoresponsive temperature can be programmed by varying the solvent component of the system.